DISEASES OF THE SUBTRACTION SYSTEM. - Qosimov Shohruh Mirzo Sherzodivich (Scholar Express Journals, 2024)
This article explores diseases of the subtraction system, a hypothetical concept that metaphorically describes the malfunction of essential processes that manage reduction, elimination, or minimization within biological or mechanical systems. Focusing on analogous systems in both human physiology and industrial machinery, the article provides insights into how "subtraction failures"—the inability to effectively remove waste or reduce inputs—can lead to dysfunctions and systemic breakdowns. It examines these processes in fields like nephrology, wastewater treatment, and electrical systems, where failure in subtraction mechanisms can severely impact performance and health.
Keywords: Subtraction system; waste elimination; physiological diseases